Copy number alterations associated with clinical features in an underrepresented population with breast cancer - Raquel M. Rodrigues‐Peres; Benilton de S.Carvalho; Meenakshi Anurag; Jonathan T. Lei; Livia Conz; Rodrigo Gonçalves; Cássio Cardoso Filho; Susana Ramalho; Geisilene R. dePaiva; Sophie F. M. Derchain; Iscia Lopes‐Cendes; Matthew J. Ellis; et al. (Molecular Genetics & Genomic Medicine, 2019)
Abstract Background As the most incident tumor among women worldwide, breast cancer is a heterogeneous disease. Tremendous efforts have been made to understand how tumor characteristics as histological type, molecular subtype, and tumor microenvironment collectively influence disease diagnosis to treatment, which impact outcomes. Differences between populations and environmental and cultural factors have impacts on the origin and evolution of the disease, as well as the therapeutic challenges that arise due to these factors. We, then, compared copy number variations (CNVs) in mucinous and nonmucinous luminal breast tumors from a Brazilian cohort to investigate major CNV imbalances in mucinous tumors versus non‐mucinous luminal tumors, taking into account their clinical and pathological features. Methods 48 breast tumor samples and 48 matched control blood samples from Brazilian women were assessed for CNVs by chromosome microarray. Logistic regression and random forest models were used in order to assess CNVs in chromosomal regions from tumors. Results CNVs that were identified in chromosomes 1, 5, 8, 17, 19, and 21 classify tumors according to their histological type, ethnicity, disease stage, and familial history. Conclusion Copy number alterations described in this study provide a better understanding of the landscape of genomic aberrations in mucinous breast cancers that are associated with clinical features.